(untitled) (Research, Society and Development, 2020)
Objective: To describe the sociodemographic and epidemiological profile of patients with chronic kidney disease undergoing hemodialysis. Methodology: This is an exploratory, descriptive and quantitative research carried out with 85 patients undergoing hemodialysis at a nephrology clinic located in Floriano/PI. Data collection was carried out in May 2017 after approval by the Research Ethics Committee under the opinion number 2.193.692, using an interview script with variables divided into two groups: sociodemographic and epidemiological, prepared by the researchers. Results: It was observed that the majority of these patients are male (65%), aged between 56 to 70 years old (36%), married marital status (60%), retired (35%), residents in the state of Piauí (83%), with incomplete elementary education (31.7%) and declared Catholic (51%). Regarding the epidemiological profile, systemic arterial hypertension (63%) was found to be the main cause of chronic kidney injury, followed by diabetes mellitus (20.5%). It was also observed that the majority of respondents have been undergoing dialysis for a long time (25.7%) and that the type of vascular access used to perform dialysis is the arteriovenous fistula (82.8%). Conclusion: In view of this, it is concluded that the identification and analysis of the profile of the patients can subsidize the health professionals working in the clinical area, facilitating the management of the activities developed in the field.